Edukasi gizi seimbang pada ibu paska melahirkan dan pencegahan stunting melalui deteksi dini neonatus - Manurung, Suryani; Amanah, Dinny Atin; Nuraeni, Ani; Rianti, Emy; Desmarnita, Ulty (JOURNAL of Public Health Concerns, 2025)
Background: Stunting remains a major health issue for toddlers in Indonesia. This remains an unresolved challenge for toddlers. Neonatal stunting is caused by multidimensional factors. Low nutritional intake and health status during pregnancy are direct causes of stunting. Purpose: To increase postpartum mothers' knowledge about preventing and detecting stunting in neonates and providing supplementary feeding to mothers after delivery to increase the quantity and quality of breast milk production. Method: The program was conducted from May to October 2025 at the Ragunan Community Health Center (Puskesmas) in Pasar Minggu District. The program was attended by the immunization and Maternal and Child Health (KIA) personnel of the Pasar Minggu District Health Center, as well as 20 postpartum mothers with neonates aged 0-28 days. The program targeted postpartum mothers with infants aged 0-1 month. The program included two educational materials: screening for early detection of neonates at risk of stunting and providing supplementary feeding to mothers after delivery. Evaluation of program achievement is assessed by analyzing the risk level of babies experiencing stunting, measuring the level of ability of postpartum mothers to implement stunting prevention programs. Results: Shows that the majority of neonates who participated in the early detection of stunting screening were male, namely 12 (60.0%) and female neonates were 8 (40.0%). The majority of maternal delivery histories were carried out by caesarean section (CS) namely 14 (70.0%) and vaginal delivery history as many as 6 (30.0%). Meanwhile, for the risk status of neonatal stunting, most were in the low category as many as 19 (95.0%) and only 1 (5.0%) was in the moderate category. Meanwhile, the average age of neonates who participated in the early detection of stunting screening was 19.5 days from the age range of 1-28 days. Meanwhile, the average stunting risk score in neonates was 1.4, with a range of 0 to 5. Conclusion: Community service activities, including education on stunting prevention through early neonatal detection, education about stunting, and providing supplementary food to postpartum mothers, were highly effective in increasing mothers' knowledge and understanding of meeting the balanced nutritional needs during the neonatal period. Increasing postpartum mothers' knowledge and understanding of appropriate food choices for neonates will positively impact the early prevention of stunting. Suggestion: It is hoped that early detection of stunting in neonates will be integrated into integrated health post (Posyandu) activities, with a clear pathway for high-risk infants. It is also hoped that future Community Service Program (PKM) activities will provide training for cadres and health workers in early detection of stunting in neonates, lactation counseling, and postpartum education for mothers. Keywords: Early detection; Health education; Neonates; Nutrition; Postpartum mothers; Stunting Pendahuluan: Masalah stunting hingga saat ini masih menjadi topik masalah kesehatan balita di Indonesia. Kejadian ini masih menjadi tantangan yang masih belum teratasi pada kelompok balita. Stunting yang terjadi pada neonatus disebabkan oleh faktor multi dimensi. Rendahnya asupan gizi dan status kesehatan pada saat kehamilan merupakan penyebab langsung dari terjadinya stunting. Tujuan: Untuk meningkatkan pengetahuan ibu pasca melahirkan tentang pencegahan deteksi dini stunting pada neonatus dan pemberian makanan tambahan bagi ibu paska melahirkan sebagai upaya dalam meningkatkan kuantitas dan kualitas produksi Air Susu Ibu (ASI). Metode: Kegiatan dilaksanakan pada bulan Mei-Oktober 2025 di Wilayah Kerja Puskesmas Ragunan, Kecamatan Pasar Minggu. Kegiatan diikuti oleh penanggung jawab imunisasi dan Kesehatan Ibu dan Anak (KIA) Puskesmas Kecamatan Pasar Minggu serta 20 peserta ibu paska melahirkan dengan neonatus berusia 0 – 28 hari. Sasaran dalam kegiatan program adalah ibu paska melahirkan dengan bayi 0-1 bulan. Kegiatan dilakukan dengan dua materi edukasi yaitu skrining deteksi dini neonatus berisiko stunting dan pemberian makanan tambahan untuk ibu paska melahirkan. Evaluasi pencapaian program dikaji dengan menganalisis tingkat risiko bayi yang mengalami stunting, mengukur tingkat kemampuan ibu paska melahirkan menerapkan program pencegahan stunting. Hasil: Menunjukkan bahwa sebagian besar jenis kelamin neonatus yang mengikuti skrining deteksi dini stunting adalah laki-laki, yaitu sejumlah 12 (60.0%) dan neonatus yang berjenis kelamin perempuan sejumlah 8 (40.0%). Mayoritas riwayat persalinan ibu dilakukan dengan sectio caessarea (SC) yaitu sebanyak 14 (70.0%) dan riwayat persalinan pervaginam sebanyak 6 (30.0%). Sedangkan untuk status risiko stunting neonatus, sebagian besar dalam kategori rendah yaitu sebanyak 19 (95.0%) dan hanya 1 (5.0%) yang dalam kategori sedang. Sementara itu, untuk rerata usia neonatus yang mengikuti skrining deteksi dini stunting adalah 19.5 hari dari rentang usia 1-28 hari. Sedangkan rata-rata skor risiko stunting pada neonatus adalah 1.4 dari rentang skor terendah 0 hingga skor tertinggi 5. Simpulan: Kegiatan pengabdian masyarakat berupa edukasi pencegahan stunting melalui deteksi dini neonatus, edukasi tentang stunting dan pemberian makanan tambahan pada ibu paska melahirkan sangat efektif dalam meningkatkan pengetahuan dan pemahaman para ibu tentang pemenuhan gizi seimbang yang dibutuhkan selama periode neonatus. Meningkatnya pengetahuan dan pemahaman para ibu paska melahirkan tentang jenis makanan yang sesuai kebutuhan neonatus akan berdampak positif terhadap pencegahan terjadinya stunting sejak dini. Saran: Diharapkan untuk tindakan deteksi dini stunting pada neonatus perlu diintegrasikan dalam kegiatan posyandu dengan alur yang jelas untuk bayi berisiko tinggi. Diharapkan juga dalam kegiatan PKM berikutnya untuk memberikan pelatihan pada kader dan tenaga kesehatan dalam melakukan deteksi dini stunting pada neonatus, konseling laktasi, dan edukasi bagi ibu paska melahirkan.